2016
DOI: 10.1021/acs.chemmater.6b00792
|View full text |Cite
|
Sign up to set email alerts
|

Composite Hydrogels with Tunable Anisotropic Morphologies and Mechanical Properties

Abstract: Fabrication of anisotropic hydrogels exhibiting direction-dependent structure and properties have attracted great interest in biomimicking, tissue engineering and bioseparation. Herein, we report a single-step freeze casting-based fabrication of structurally and mechanically anisotropic aerogels and hydrogels composed of hydrazone cross-linked poly(oligoethylene glycol methacrylate) (POEGMA) and cellulose nanocrystals (CNCs). We show that by controlling the composition of the CNC/POEGMA dispersion and the free… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
161
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 217 publications
(176 citation statements)
references
References 74 publications
(172 reference statements)
6
161
2
Order By: Relevance
“…[109] Our group has shown that the incorporation of rigid rod-like CNCs increased the compressive modulus of freeze-casted macroporous poly(oligoethylene glycol methacrylate) (POEGMA) hydrogels by nearly one order of magnitude as the CNC concentration was increased from 0.4 to 1.2 wt%. [113] Finally, Khademhosseini and co-workers have shown that the incorporation of CNT into photocrosslinkable gelatin methacrylate (GelMa) hydrogels led to a >threefold increase in compressive modulus (Figure 3). [112] When seeded with cardiomyocytes, these hydrogel scaffolds show promise as functional cardiac patches.…”
Section: High-strength Hydrogelsmentioning
confidence: 98%
See 2 more Smart Citations
“…[109] Our group has shown that the incorporation of rigid rod-like CNCs increased the compressive modulus of freeze-casted macroporous poly(oligoethylene glycol methacrylate) (POEGMA) hydrogels by nearly one order of magnitude as the CNC concentration was increased from 0.4 to 1.2 wt%. [113] Finally, Khademhosseini and co-workers have shown that the incorporation of CNT into photocrosslinkable gelatin methacrylate (GelMa) hydrogels led to a >threefold increase in compressive modulus (Figure 3). [112] When seeded with cardiomyocytes, these hydrogel scaffolds show promise as functional cardiac patches.…”
Section: High-strength Hydrogelsmentioning
confidence: 98%
“…The incorporation of nanoparticles such as graphene oxide (GO), [108,109] silver nanoparticles, [110] hydroxyapatite nanoparticles, [111] carbon nanotubes (CNT), [112] cellulose nanocrystals (CNCs), [35,113,114] and others have been used as reinforcing agents in macroporous hydrogels, with varying amounts of success. Notably, Huang et al demonstrated that strong intermolecular interactions between GO and chitosan leads to the self-assembly of supramolecular macroporous composite hydrogels demonstrating enhanced mechanical performance versus chitosan-only gels.…”
Section: High-strength Hydrogelsmentioning
confidence: 99%
See 1 more Smart Citation
“…• Time/energy-consuming during freezing [94][95][96][97][98] Self-assembly Nanoparticles (0D) Nanotubes (1D) Nanosheets (2D) Nanolamellae (2D)…”
Section: Magnetic Fieldsmentioning
confidence: 99%
“…For example, cellulose nanocrystals (CNCs) have attracted attention as 1D nanocomponents due to their mechanical strength, commercial availability, and biocompatibility. [92][93][94] By controlling the composition of the CNC/polymer dispersion and the freeze-casting temperature, hydrogels with fibrillar, columnar, or lamellar internal morphologies can be obtained; these morphologies are analogous to the directional structures of biological soft tissues. Thus, fabricated composite hydrogels with ordered CNC structures exhibit high mechanical anisotropy.…”
Section: Freeze-castingmentioning
confidence: 99%